Effect of Confining Pressure on Mechanical and Energy Conversion Properties of Gas-Containing Coal under Loads - Zhizhen Zhang; Yixin Niu; Xiaoji Shang; Rui Zhou; Xingguang Liu; Feng Gao (Geofluids)
Confining pressure is closely related to the deformation and failure characteristics of gas-containing coal and is one of the key factors for gas outburst-rockburst coupled dynamic disaster. Firstly, this paper briefly summarized the triaxial compression test results of gas-containing coal under different confining pressures, including deformation and stiffness and failure and strength. Then, based on the second developed MatDEM gas-solid coupling program, the macro- and microdeformation and failure process of coal samples under different confining pressures and constant gas pressure were simulated, and the distribution of particle stress, pore stress, and crack, as well as energy conversion characteristics, was obtained. Finally, the influence mechanism of confining pressure on deformation and failure of gas-containing coal was discussed, and the occurrence conditions of coal and gas outburst, rockburst, and their coupled dynamic disasters were distinguished. The results show that the peak strength and residual strength after failure of gas-containing coal both increase approximately linearly with the increase of confining pressure, while the elastic modulus does not change much or increases continuously, which is closely related to the number of microdefects in the coal sample. The strengthening effect of confining pressure on rock stiffness and strength mainly comes from external support and compaction. The total number of cracks decreases with the increase of confining pressure, while the number of shear cracks increases, and the inclination angle between the formed macroscopic main crack and the horizontal plane gradually decreases. The maximum cumulative elastic energy and residual elastic energy both increase with the increase of confining pressure, which leads to the increase of the impact tendency index of coal samples.